Two newly identified, relatively old star clusters in the Small Magellanic Cloud - Piatti, Andres Eduardo (2007)
We present the results on the age and metallicity estimates of the Small Magellanic Cloud (SMC) clusters L110, L112 and L113 obtained from CCD Washington CT1 photometry. We confirm L113 as a relatively old and metal-poor cluster, and report for the first time that L110 and 112 are also relatively old clusters (t ~ 6.5 Gyr). Their derived ages and metallicities reinforce previous suggestions that the farther a cluster is from the centre of the galaxy, the older and more metal-poor it is, with some dispersion. In addition, the bursting star formation model still appears to be the most probable paradigm to describe the SMC´s star formation history. We call attention to a second possible burst at ~6-7 Gyr, besides the known burst at ~3 Gyr.